X-ray photoelectron spectroscopy of the interface formation on cleavage surfaces of the layered semiconductor In₄Se₃ crystals - Galiy, P.V.; Musyanovych, A.V. (Functional Materials, 2005)
The results of X-ray photoelectron spectroscopy of the phase interface formation on the cleavage surfaces of layered semiconductor In₄Se₃, In₄Se₃(Cu) crystals are presented. The peculiarities of the process in the high-vacuum chamber atmosphere have been studied using the Auger electron spectroscopy. The carbon and oxygen interface coatings are formed due to interaction of the air with atomically clean cleavage surfaces of the crystals pure In₄Se₃ and In₄Se₃(Cu) crystals. Представлены результаты исследования формирования междуфазных границ на поверхностях скалывания кристаллов слоистых полупроводников In₄Se₃, In₄Se₃(Cu), полученные методом рентгеновской фотоэлектронной спектроскопии (РФЭС). Особенности этого процесса в атмосфере остаточных газов сверхвысоковакуумной камеры исследованы методом оже-электронной спектроскопии (ОЭС). Углерод-кислородные интерфейсные покрытия на междуслойных поверхностях скалывания формируются вследствие взаимодействия воздуха с атомарно чистыми поверхностями скалывания кристаллов. Представлено результати дослiдження формування мiжфазових меж на поверхнях сколювання кристалiв шаруватих напiвпровiдникiв In₄Se₃, In₄Se₃(Cu), одержанi методом рентгенiвської фотоелектронної спектроскопiї. Особливостi цього процесу в атмосферi залишкових газiв надвисоковакуумної камери дослiджено методом оже-електронної спектроскопiї. Вуглецево-кисневi iнтерфейснi покриття на мiжшарових поверхнях сколювання формуються у результатi взаемодiї повiтря з атомно чистими поверхнями сколювання кристалiв.